DAKON MEDIA WITH GUIDED DISCOVERY TO IMPROVE PRIMARY STUDENTS’ MATHEMATICAL UNDERSTANDING AND REASONING - Yunia Kurniasih; Fery Muhamad Firdaus; Setiawan Edi Wibowo (Universitas Majalengka, 2026)
Conceptual understanding and mathematical reasoning are essential foundations for students’ mastery of multiplication and division in primary school. The initial classroom diagnosis showed that many third-grade students still learned multiplication and division procedurally and had difficulty connecting concrete situations, visual representations, and mathematical symbols. This classroom action research aimed to improve students’ conceptual understanding and mathematical reasoning through dakon mathematics media integrated with Guided Discovery Learning and the Concrete–Representational–Abstract pathway. The study involved 31 third-grade students of SD Muhammadiyah Sapen Yogyakarta during January and February 2026 in the second semester of the 2025/2026 academic year. The action was conducted in two cycles consisting of planning, action implementation, observation, and reflection. Data were collected through conceptual understanding tests, mathematical reasoning tasks, observation sheets, and brief interviews. The findings showed that students’ conceptual mastery improved progressively. The percentage of students achieving mastery increased from 32.26% in the pre-action stage to 58.06% in Cycle I and 77.42% in Cycle II. The class average increased from 69.35 in Cycle I to 79.35 in Cycle II. Mathematical reasoning improved from a mean score of 8.71 in Cycle I to 9.68 in Cycle II. These results indicate that dakon media, when supported by guided discovery and structured representational transition, can strengthen students’ conceptual connections, justification, strategy comparison, and answer verification. The study concludes that culturally familiar manipulatives are effective when their use is integrated with reflective questioning and systematic representation.